ANALISIS EFISIENSI INTEGRASI (MACRO VBA) PADA MICROSOFT EXCEL DAN OUTLOOK SEBAGAI SISTEM INFORMASI PT ABC - Revina Salsya Wijaya; Theodorus Sendjaja (Jurnal Manajemen dan Teknologi Informasi, 2025)
The use of Microsoft Excel and Outlook integrated using (Macro VBA) in information systems in companies can improve the efficiency of employee performance. This study aims to analyze the level of efficiency of Excel integration with Outlook in facilitating daily work, both in the context of file delivery time management and real-time access to work documents. A qualitative approach is used as a method to provide a descriptive view of the efficiency of the integration of Microsoft information systems in the company. This method is carried out by direct observation and interviews with company employees who use Excel and Outlook every day in completing their work. From the research results, it is stated that the integration of the information system can provide better file delivery time efficiency and avoid wasting time in sending work files to superiors. In addition, employees get good added value from superiors because they are disciplined in sending their work files or documents. This has a big impact on the KPI (Key Performance Indicator) of employees to improve the quality of their work in the company. Therefore, this research can be a reference basis for consideration to improve employee competence in using integration between Excel and Outlook in the company.